Natural Genotypic Variation Underpins Root System Response to Drought Stress in Bambara Groundnut [Vigna subterranea (L.) Verdc.] - Mateva, Kumbirai Ivyne; Chai, Hui Hui; Mayes, Sean; Massawe, Festo (Frontiers in Plant Science, 2022)
Bambara groundnut (Vigna subterranea (L.) Verdc.) is grown in rainfed production systems and suffers from periodic drought stress leading to yield reductions. Natural genetic variation for root traits is essential for adaptation to water deficit conditions. However, root traits have not been fully utilised as selection criteria to improve drought stress in bambara groundnut. The present study explored the natural genetic variation found in single genotypes of bambara groundnut derived from landraces to identify adaptive differences in tap root length (TRL) and root length density (RLD) in response to drought stress. A diverse core collection of eight bambara groundnut genotypes (namely, Gresik, LunT, IITA-686, DodR, S19-3, Tiga nicuru, Ankpa-4, DipC1), were grown for two seasons (2018 and 2019) in polyvinyl chloride (PVC) columns in well-watered (WW) and 30-day drought stress (DS) treatments. Plant samples were collected at 55 days after emergence (DAE) (late flowering) and at 105 DAE (50-d of recovery). The results show that DS significantly (P < 0.05 - < 0.001) reduced shoot height (SH), number of leaves (NoL) and delayed flowering in 2018 and 2019 except for one genotype (LunT) in 2018. Root to shoot (R:S) ratio was significantly higher (P < 0.001; 22%) under DS in 2018. Under DS, average tap root length (TRL) at 55 DAE was significantly decreased by 14% and 22% in 2018 and 2019 and by 5% and 11% at 105 DAE (50-d of DS recovery) in 2018 and 2019, respectively. Average root length density (RLD) under DS treatment was associated with substantial grain yield advantage (R2 = 0.27 and R2 = 0.49) in 2018 and 2019, respectively. Variation in intrinsic RLD in deeper soil depths in the genotype DodR determines root foraging capacity when facing drought stress. This suggests that different agroecological environments to which bambara groundnut is subjected in its natural habitat have promoted a phenotypic differentiation — in root system, to adapt to ecotypic conditions, which may help offset the impact of drought stress. The natural genetic variation exhibited especially by DodR could be exploited to identify potential quantitative trait loci (QTL) controlling deep rooting and root length density.